2019
DOI: 10.1123/kr.2019-0016
|View full text |Cite
|
Sign up to set email alerts
|

Maltreatment in Youth Sport: A Systemic Issue

Abstract: The recent, highly publicized cases of maltreatment of athletes have garnered critical attention by the public at large and stakeholders in sport, alike. For many, these cases threaten popular views that sport contributes in important ways to positive youth development. The growing evidence showing that maltreatment occurs to youth sport participants highlights the need for safe, harm-free sport environments as a fundamental prerequisite for positive developments to be reaped. By unpacking the case study of US… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(31 citation statements)
references
References 28 publications
1
19
0
Order By: Relevance
“…This study confirms that the quality of coach-athlete interpersonal interactions depends on a broader organizational context ( Lazarević et al, 2015 ; Stefaniuk and Bridel, 2018 ; Parent and Fortier, 2018 ; Kerr et al, 2019 ). The results of the study enabled to distinguish the determinants promoting bullying in sport, which can be relatively divided into groups covering three different levels ( Figure 2 ).…”
Section: Discussionsupporting
confidence: 86%
“…This study confirms that the quality of coach-athlete interpersonal interactions depends on a broader organizational context ( Lazarević et al, 2015 ; Stefaniuk and Bridel, 2018 ; Parent and Fortier, 2018 ; Kerr et al, 2019 ). The results of the study enabled to distinguish the determinants promoting bullying in sport, which can be relatively divided into groups covering three different levels ( Figure 2 ).…”
Section: Discussionsupporting
confidence: 86%
“…Also, in line with previous studies ( Alexander et al, 2011 ; Hauw et al, 2021 ), our results highlighted that the perpetrators of psychological and sexual violence in the sport context were mainly peers. Conversely, Kerr et al (2019) observed that most psychological violence was experienced from coaches, followed by peers. Regarding the French-speaking Swiss prevalence rates, Hauw et al (2021) found reports of 87% psychological, 37.7% physical, and 32.8% sexual violence among former athletes, whereas we observed that 75.3% of our participants declared psychological violence, 52.9% physical violence, and 27.9% sexual violence.…”
Section: Discussionmentioning
confidence: 96%
“…Kerr and Kerr ( 2020 ) offered a critique of the interventions that have been implemented internationally to address safe sport and protect athletes from harm. As athlete maltreatment is a systemic issue requiring safeguarding interventions that extend from the individual to the organisational and societal levels (Kerr et al, 2019 ), Bronfenbrenner's ( 1979 ) Bioecological Systems Theory was used to address safeguarding strategies at each level of the theory. At the individual level, athletes' knowledge and awareness of safe sport-related topics are encouraged through the delivery of educational programmes.…”
Section: Introductionmentioning
confidence: 99%
“…Previous researchers have recommended that ensuring safe sport is the responsibility of all adults in the sport (Brackenridge, 2001 ; Kerr et al, 2019 ), and it may be argued that sport administrators hold a particularly important position of influence. Sport administrators have positions of power and authority over the operations of the organisation, including funding allocations, staffing decisions, implementation of policy and procedures, risk management and legal issues and accountability.…”
Section: Introductionmentioning
confidence: 99%